Treatment of Fulminant Hepatic Failure – Is There Light at the End of the Tunnel? - KDE Kaita (Canadian Journal of Gastroenterology)
A lot of research has been done on fulminant hepatic failure (FHF), mainly because of the high mortality associated with it. Many centres continue to search actively for the ideal medical treatment for FHF because liver transplantation is often difficult in these very ill patients. The many forms of therapy that have been tried and reported in case reports, small clinical trials and the occasional randomized controlled trial are reviewed, as are the current data on bioartificial livers and isolated hepatocyte transplantation. The ideal treatment remains elusive, and more work needs to be done to find a highly effective form of therapy for these very ill FHF patients.